PROSPEK PENGEMBANGAN PERIKANAN TANGKAP DI PERAIRAN PROVINSI RIAU - T. Ersti Yulika Sari; Sugeng Hari Wisudo; Daniel R. Moninjta; Tommy Purwaka (Buletin PSP, 2009)
A proper strategy for fisheries management is needed in enforcing sustainable fisheries resource management.  The selected fisheries should consists various component of fishing unit which can be operated technologically and ecologically in sustainable manner.  In order to know the selected fish resources of Riau Province especially after the separation of Riau Kepulauan from Riau Province, evaluation was conducted on Bengkalis Regency in Malacca Strait and Indragiri Hilir Regency in South Chine Sea.  Survey method was used to collecting information and data from the field.  Schaefer model was used to determine the limit of fishery utilization by determining the Maximum Sustainable Yield (MSY).  Linear Goal Programming (LGP) Model was used to analyse the fishing unit allocation based on all determined target.  Scoring method was applied to indicate the best kind of capture fisheries technology.  The results of this study indicated that selected fish resource in Malacca Strait Bengkalis Regency are, yellow pike-conger, giant threadfish, silver pomfret, and white shrimp, with fishing technology of  longline, kurau net, atom net and apollo net.  The optimum amount for  the selected fishing technology in Bengkalis Regency is 6387 unit.  Selected fish resources in the South China Sea Indragiri Hilir Regency are giant threadfish, white shrimp, yellow pike-conger  and barred spanish mackerel and with fishing technology of longline, “kurau net”, gillnet and shrimp net.  The optimum amount for the selected fishing technology in Indragiri Hilir Regency is 5825 unit. Key words:  Malacca Strait, optimum amount, selected fishing technology, selected fish resources, South China Sea